2015
DOI: 10.14252/foodsafetyfscj.2015011
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Di(2-ethylhexyl) phthalate and Subsequent Infant and Child Health Effects

Abstract: Because fetuses are considered the most sensitive to di(2-ethylhexyl) phthalate (DEHP) exposure, the effects of maternal exposures during pregnancy on infant and child health were reviewed from recently reported studies. The major modes of exposure to this chemical are food and indoor air; hence, it remains important to decrease the risk of exposure from contaminated foods. Although DEHP metabolic profiles were not different between pregnant and non-pregnant women, metabolic rates appeared lower in late pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…MEHP can be further metabolized to CYP-mediated mono(2-ethyl-5-hydroxyhexyl) phthalate (5-OH MEHP), mono(2-ethyl-6-hydroxyhexyl) phthalate (6-OH MEHP), 5 oxo-MEHP (MEOHP), mono(2carboxymethyl-hexyl) phthalate (2cx-MMHP) and mono(2-ethyl-5-carboxypentyl) phthalate (MECPP) with the hydroxylation of carbon side chains (Ito et al 2014, Nakajima et al 2015. Of these, the carbon side chain of metabolites can be further cleaved to phthalic acid by O-dealkylation (Choi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MEHP can be further metabolized to CYP-mediated mono(2-ethyl-5-hydroxyhexyl) phthalate (5-OH MEHP), mono(2-ethyl-6-hydroxyhexyl) phthalate (6-OH MEHP), 5 oxo-MEHP (MEOHP), mono(2carboxymethyl-hexyl) phthalate (2cx-MMHP) and mono(2-ethyl-5-carboxypentyl) phthalate (MECPP) with the hydroxylation of carbon side chains (Ito et al 2014, Nakajima et al 2015. Of these, the carbon side chain of metabolites can be further cleaved to phthalic acid by O-dealkylation (Choi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MEHP can be further metabolized to CYP-mediated mono (2-ethyl-5-hydroxyhexyl) (Ito et al 2014, Nakajima et al 2015. Of these, the carbon side chain of metabolites can be further cleaved to phthalic acid by O-dealkylation (Choi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally findings from previous studies suggested that urinary DEHP metabolites in pregnant women were lower, particularly at the later stages of pregnancy than those in non-pregnant women, thus using urinary DEHP metabolites as exposure biomarkers needs to be cautiously implemented 46 . Other limitations were the follows.…”
Section: Discussionmentioning
confidence: 99%